Evaluation of an electric vehicle (EV) disposal process and benchmarking on the EV technology - Choy, Jia Qi (2023)
The global shift towards electric vehicles (EVs) as an eco-friendly transportation solution has accelerated, driven by environmental awareness and climate change concerns. However, EV sustainability poses multifaceted challenges surrounding the end-of-life disposal issues, and questions surrounding long-term performance. This research aims to explore the current vehicle disposal process and benchmark the EV technology. The outcome of this aim will evaluate the disposal process as well as the performance of modern electric vehicles. It includes a literature review of current EV disposal methods, encompassing recycling and component reuse, alongside hands-on disassembly of an aging EV conversion project vehicle. Additionally, computer software simulations will benchmark EV technology, offering insights into its performance in the transportation sector. The research revealed severe battery deterioration in the aging EV conversion project vehicle, and the project vehicle was sustainably disposed. The performance of modern electric vehicles has improved significantly over the decade, making them a viable zero emissions transportation solution. Simulations demonstrated a 4.48% of range loss when electric vehicles are driven on 0.6 mm water film thickness at 30 km/h speeds. Additionally, an average of 2.66% range loss per 100 kg increase in loading was recorded. A case study regarding the number of trips that can be completed between UTAR Sg Long and MRT Bukit Dukung has shown that modern electric vehicles can meet the daily needs of daily commuters while producing zero emissions. Lastly, a reduction of 38.77% in gear ratio enhanced the range of the 2015 Volkswagen e-Golf simulation model by 8.62% at higher speeds. The findings from this research contribute valuable insights for future improvements and sustainability initiatives within the EV industry. In a summary, current electric vehicle disposal processes were found to be manual intensive, which leads to opportunities for more automation in this sector. Electric vehicle technology has also improved and is able to meet the daily needs of a city commuter. In the future, the research can be improved by incorporating new electric vehicle technology such as solid-state batteries and sodium ion batteries into the simulator.